Three scenarios for the Qatar crisis: Regime change, resolution or Cold War in the Gulf - Matthias Sailer; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2017)
On 5 June 2017 Saudi Arabia, the United Arab Emirates (UAE), Egypt and a number of allied states broke off diplomatic relations with Qatar and imposed a partial blockade. Their stated demand was for Qatar to cease its support for "terrorist" groups and its policy of "destabilising" other countries. With Qatar rejecting the charges as baseless, the prospects for resolution appear thin. The most conceivable scenarios are forcible replacement of the Qatari leadership, peaceful resolution between the parties, or consolidation of the rift between two camps in the Gulf. Germany and other European states should avoid taking sides, but should assert three fundamental demands: the conflict parties must respect national sovereignty and the proportionality required by international law, refrain from instrumentalising the fight against terrorism, and prevent the dispute spilling over into other conflicts in the region.
Keywords: 320